Pengaruh Tingkat Kesejahteraan Karyawan, Komunikasi, dan Lingkungan Kerja terhadap Semangat Kerja Karyawan di SMK 1 Islam Taruna Krembung Sidoarjo - Machfudz Efendi; Dewi Andriani; Bayu Hari Prasojo (Universitas Muhammadiyah Sidoarjo, 2017)
The purpose of this study was to find out how much influence the variable level of welfare, communication, and work environment had on the work morale of teachers and employees of SMK 1 ISLAM TARUNA KREMBUNG-SIDOARJO simultaneously. This research was conducted with quantitative methods. The data collection technique used was a questionnaire with a sample of 34 people. The data analysis technique used in this study is multiple linear regression using the SPSS program. The results of the study based on the F test show that the level of welfare, communication, and work environment together influence the work morale of teachers and employees. While based on the t test, the variable level of welfare and work environment does not significantly influence work morale. While communication has a significant effect and has the largest t-count compared to the other variables.